Effect of Feed Form on Body Conformation Traits of Different Hybrids of Broiler Chickens - Oluwabukola Olayemi Lawrence Azua; Gelaye Gebisa; Oda Gizaw (International Journal of Zoology)
This research was conducted to measure the exterior characteristics in four hybrids of broilers fed pelleted and commercial mash feed. A total of 112 one-day-old chicks from four broiler hybrids, namely, Arbor Acre, Cobb 500, Marshall, and Ross 308 were used for this experimentation and allocated into four treatments with 28 birds of each hybrid and were replicated four times with 7 birds per replicate in a 2 × 4 factorial experiment. Pelleted and milled (mash) commercial feed was used for this experiment. The feeding trial lasted at the age of 59 days old, and data on the conformation trait were recorded. The results of the conformation traits showed no significant difference (P>0.05) in any of the parameters measured. Most of the conformation traits examined were positive and strongly correlated with one another. Finally as a suggestion, further deep study needed to be conducted by considering different factors including an interaction effect of the main factors.